Candida Periprosthetic Joint Infection: Is It Curable? - Laura Escolà-Vergé; Dolors Rodríguez-Pardo; Pablo S. Corona; Carles Pigrau (MDPI AG, 2021)
Candida periprosthetic joint infection (CPJI) is a rare and very difficult to treat infection, and high-quality evidence regarding the best management is scarce. Candida spp. adhere to medical devices and grow forming biofilms, which contribute to the persistence and relapse of this infection. Typically, CPJI presents as a chronic infection in a patient with multiple previous surgeries and long courses of antibiotic therapy. In a retrospective series of cases, the surgical approach with higher rates of success consists of a two-stage exchange surgery, but the best antifungal treatment and duration of antifungal treatment are still unclear, and the efficacy of using an antifungal agent-loaded cement spacer is still controversial. Until more evidence is available, focusing on prevention and identifying patients at risk of CPJI seems more than reasonable.